Modelling and Analyses of Fiber Fabric and Fabric-Reinforced Polymers under Hypervelocity Impact Using Smooth Particle Hydrodynamics. (October 2020) - Zhao, Shicao; Song, Zhenfei; Espinosa, Horacio D.
Highlights: In a Whipple shield against HVI, the lightweight alloy is preferable for bumper material, while advanced fiber fabrics are candidate materials for its filler layer. The plain weave fabric possesses the best performance in kinetic energy absorption among simulated fabrics including the 3D orthogonally-woven fabric. The performance of lightweight alloy – fabric layer hybrid laminates correlates with the decay of shock wave resulting from HVI, and the presence of interfaces contributes to shielding capability. Corrugated plate and associated gap is beneficial to shielding performance. Abstract: In a hypervelocity impact (HVI) event, fiber fabrics and the fabric-reinforced polymers (FRP) would undergo shock compression, large deformation and fragmentation. The smooth particle hydrodynamics (SPH) approach was applied to assess the shielding performance of the fabric and its composite structure in a Whipple shield. In the fabric model, a fiber is built by SPH particles to properly reproduce the spreading feature of fragmented fabric under HVI. The simulations display that an aluminum panel, serving as the bumper of a Whipple, has the better performance in debris spreading than fabric layers. In the stuffed layer of a Whipple, the widely used plain weave fabric has the similar performance as the 3D weave both in debris spreading and speed retarding. The fabric model is further developed and extended to FRP by building fiber and polymer materials separately based on specific geometries. The computations illustrate that the FRP/Aluminum hybrid laminate can efficiently reduce the shock peak under HVI and meanwhile produce large deformation for kinetic energy absorption, in good agreement with experimental measurements. It applies to the rear wall of a Whipple which should resist the HVI of a debris cloud, forming a high but short shock pulse. The further optimization of the hybrid laminate was made by using a corrugated aluminum plate, a gap and a Kevlar fabric layer, leading to the considerable reduction of the laminate areal mass in a prescribed thickness.